Comparison between 3D delta plate and conventional miniplate in treatment of condylar fracture: A randomised clinical trial. Issue 11 (November 2021) - Ganguly, Aneesh; Mittal, Gaurav; Garg, Ritesh
Abstract: The aim of the study was to conduct a randomized clinical trial comparing the efficacy of standard non-compression miniplate and 3-dimensional (3D) titanium plate in the open reduction internal fixation (ORIF) of the mandibular condylar fractures. Patients who underwent open reduction of mandibular condylar fracture were recruited for the study. The patients satisfying the inclusion criteria were randomly assigned to two groups in a 1:1 ratio. Group A comprised patients treated using conventional miniplates, and Group B comprised patients treated using 3D Delta Plate. Informed consent was provided. All the patients underwent ORIF under GA via retromandibular approach. The sample size was set at 20 participants, with 10 participants in each group who were randomly allocated. Our study showed that patients in Group A had a significant statistical difference operating time (141.20 ± 2.59 min) than that of Group B (117.2 ± 9.63 min). Mouth opening was significantly greater in the 3 rd -month follow-up in Group B (mean = 42.40 ± 1.82) compared to Group A (mean = 35.80 ± 1.30). Biting efficiency in Group B was observed to be clinically and statistically better compared to Group A (P = 0.012). Wound dehiscence was managed efficiently by judicious use of antibiotics and wounds were free of any signs of infections or discharge in the consecutive follow-ups. No plate removal was required in either group. Patients treated with 3D delta plates have superior outcomes with regard to operation time, mouth opening, and biting efficiency compared with miniplates. Hence, it can be concluded that the triangular shape of the 3D Delta plate allows the stress distribution to be superior and multidimensional, leading to better post-operative stability, faster healing, and reduced complications.